Proses Penanganan Pembiayaan yang Bermasalah di Koperasi Simpan Pinjam BMT Amana Sejahtera - Mariana Mariana; Tutut Dewi Astuti (Jurnal Akuntan Publik, 2024)
The process of handling financing aims to identify strategies for addressing problematic financing in savings and loan cooperatives or BMT (Baitul Maal Wat Tamwil). The research method employed is qualitative, utilizing structured interviews, field observations, and documentation for data collection. The primary factors contributing to problematic financing in BMTs are identified as internal factors (suboptimal analysis of documents and adherence to financing standard operating procedures) and external factors (dishonesty and untrustworthiness among members, malicious intentions, procrastination by members, and unintentional factors such as relocation and natural disasters). Handling strategies involve communication via mobile phones (WhatsApp messages or calls), issuing warning letters, and executing collateral. Efforts to mitigate problematic financing include strict adherence to standard operating procedures, adequate task allocation, the application of prudence principles, and enhancement of employee skills.